2004
DOI: 10.1080/02841860310017973
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in survival in non-small cell lung cancer patients 1974–1998

Abstract: This study comprised a total of 7,553 patients with non-small cell lung cancer (2,660 women and 4,893 men) treated at a comprehensive cancer centre between 1974 and 1998. Significant differences in tumour histology were associated with gender (p < 0.001); adenocarcinoma was the most common diagnosis in both men (50.0%) and women (41.7%); squamous cell carcinoma was the second most prevalent diagnosis (21% and 31% in women and men, respectively); and bronchioalveolar tumours were more prevalent in men (3% compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 20 publications
4
32
2
1
Order By: Relevance
“…It has been proposed that the improved survival of lung cancer patients over time might be attributed in part to the increased incidence of lung cancer in women, and the observation that women with NSCLC generally have better survival outcomes than men [16,17]. However, in our survival analysis, female gender was not a significant predictor of longer survival.…”
Section: Discussioncontrasting
confidence: 54%
“…It has been proposed that the improved survival of lung cancer patients over time might be attributed in part to the increased incidence of lung cancer in women, and the observation that women with NSCLC generally have better survival outcomes than men [16,17]. However, in our survival analysis, female gender was not a significant predictor of longer survival.…”
Section: Discussioncontrasting
confidence: 54%
“…[3][4][5][6][7][8]10,11 For example, in a prospective study of 1085 patients with stage I to III NSCLC, Cerfolio et al found that women had a significantly higher 5-year OS rate than men (60% vs 50%; P < .001). 3 In that study, OS rates for both sexes were higher than in ours, most likely because their patients were seen in a surgical clinic, which limited the study population to patients who were surgical candidates.…”
Section: Discussionmentioning
confidence: 99%
“…6,21,22 Therapeutic disparities may also influence the survival of men and women with NSCLC, 10,23,24 but it has been shown that the OS advantage for women persists regardless of treatment received. 7,10,12 To our knowledge to date, no study has provided a thorough analysis of whether sex influences the treatment or outcome of NSCLC patients receiving radiation. Previous studies have been limited by differences in radiation dose and technique among institutions, incomplete radiation records in population-based registries, and the confounding relationship between disease stage and the use of radiation as a treatment.…”
mentioning
confidence: 99%
“…Most patients are diagnosed at a late clinical stage, and despite significant improvements in conventional therapies for lung cancer, the overall 5-year survival remains poor [2].…”
mentioning
confidence: 99%